SISTEM INFORMASI REKAM MEDIS PASIEN PADA KLINIK ARTERI SEMARANG BERBASIS WEB (Information Technology and Telematics, 2015)
Abstract - Medical record system of patients during an artery semarang clinics located in in semarang , precisely in jl.soekarno-hatta no.65 semarang. During this artery of the system at the clinic semarang still use the manual, and often experienced many obstacles are necessary quite a long and convoluted process, the assessment of invalid calculations because of not using appropriate formula. Record system medical patient dikembangan by using a system of prototyping by using a programming language PHP and MySQL database. Of a record system medical developed margani revealed by using a system of prototyping by using a programming language php and mysql database . The system made to facilitate the management of medical record data, the management of data on medical costs information to patients and medical record data for computerized patient . Data collection method that is used is a field study covering the interview or question and answer directly systematically with the clinic manager artery semarang . The study of literature can be taken by how to read and study the literature books that deals with record system medical patient . Keywords: record system medical patient, php, mysql, a method of prototyping